Phenotypic and genotypic characterization of Shiga toxin-producing Escherichia coli strains recovered from bovine carcasses in Uruguay - Mussio, Paula; Martínez, Inés; Luzardo, Santiago; Navarro, Armando; Leotta, Gerardo; Varela, Gustavo (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen that cause food-borne diseases in humans. Cattle and derived foodstuffs play a known role as reservoirs and vehicles, respectively. In Uruguay, the meat industry is one of the main economic activities, however information about the characteristics of circulating STEC in this productive chain is scarce. The aim was to characterize phenotypically and genotypically a set of 39 STEC recovered from 800 bovine carcasses located in maturation chambers of different slaughterhouses, using classical microbiological procedures and Whole Genome Sequencing (WGS). STEC from 20 establishments were characterized in detail. They belonged to 21 diﬀerent O-groups and 13 diﬀerent H-types. Only one O157:H7 strain was characterized and the serotypes O130:H11(6), O174:H28(5) and O22:H8(5) prevailed. One strain showed resistance in vitro to tetracycline and genes for doxycycline, sulfonamide, streptomycin and fosfomycin resistance were detected. Thirty-three strains (84.6%) carried the subtypes Stx2a, Stx2c or Stx2d. The gene eae was detected only in two strains (O157:H7, O182:H25). The most prevalent virulence genes found were lpfA (n=38), ompA (n=39), ompT (n=39), iss (n=38) and terC (n=39). Within the set of STEC analyzed, the majority (81,5%) belonged to FAO/WHO´s risk classification levels 4 and 5 (lower risk). Besides, we detected STEC serotypes O22:H8, O113:H21, O130:H11 and O174:H21 belonged to level risk 2 associate with diarrhea, hemorrhagic colitis or Hemolytic-Uremic Syndrome (HUS). The only O157:H7 strain analyzed belonged to ST11. Thirty-eight isolates belonged to the Clermont type B1, while the O157:H7 was classified as E. This is the first local work which incorporates a detailed study about STEC present in chilled carcasses. The analyzed STEC showed high genomic diversity and harbor several genetic determinants associated with virulence, underlining the important role of WGS for a complete typing. In this set we did not detect non-O157 STEC previously isolated from local HUS cases. However, when interpreting this findings, the low number of isolates analyzed and some methodological limitations must be taken into account. Other studies are needed to assess the role of the local meat chain in the spread of STEC, especially those associated with severe diseases in humans.